La Station Nation du RER A. Un patrimoine souterrain - Raphaël Labrunye; Raphaël Lescure (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
As works for building the future Grand Paris Express rapid transit network are starting, the RATP Group initiates important modernization works of the regional high-speed RER A stations. In order to prevent any unfortunate destruction, the public transport operator seek to develop a singular approach by creating a scientific committee on heritage / heritage advisory board. A historical study was thus conducted on Paris intramuros stations (including ‘La Defense’) and focused on the ‘Nation’ station designed by the architect Alain Bourbonnais. By the end of the 1960s, the RATP Group was facing a major undertaking, which radically changed the scales and issues therefore associated with underground lines construction. The ambition / The aim was to build a confortable transportation infrastructure open to all social classes. Pursuing a proven approach, the RATP Group hired consulting architects who were the designers of a new aesthetic sense of the metropolitan transportation. Major innovations such as a new ticket checking system, use of Emaux de Briare ceramic coatings, display of artworks and shops were gathered to convey a true idea of underground urbanism. Excluded from structural engineering phases, architects tried there best to adapt to an oversized shell which was designed to manage complex flows of people. The result is a unique piece of art which remains close to its original condition. The underground situation unfortunately implies total dismantling of the existing decor and the overall renovation project is a major challenge to the traditionnal open air heritage approach.